An Investigation of the Efficiency in Nigeria Real Estate Agency Practice - Iroham, C. O.; Oluwunmi, A. O.; Ayedun, C. A.; Oloyede , S. A. (Mediterranean Journal of Social Sciences, 2011)
Estate agency which has been researched upon particularly in the UK, US and Asia is still in its infancy in Nigeria. Thisresearch aims at discovering the impact of different agency types in the efficiency of Nigeria real estate practice. The study of 159 EstateSurveying firms and 91 Property development companies in the commercial nerve centre of the country (Lagos) representing both agentsand principal (vendor/purchasers) respectively, indicates that multiple agency is mostly adopted in Nigeria real estate practice. TheRelative Important Index coupled with Chi-Square test at 0.05 level of significance supports the posit of certain inefficiencies synonymouswith multiple agency as discovered in an earlier work carried out in the UK. The researchers thereby advocated the modification of subagencypractice particularly to involve the consent and commitment of principals so as to eradicate all inefficiencies by safeguarding theinterest of all parties. A call for focus on the neglected real estate agency research among Nigeria researchers is also advocated.